2009
DOI: 10.1007/s00423-008-0461-9
|View full text |Cite
|
Sign up to set email alerts
|

Fournier’s gangrene: is the female gender a risk factor?

Abstract: The female gender is a risk factor for mortality in patients with Fournier's gangrene and is associated with a higher incidence of inflammation of the retroperitoneal space and abdominal cavity. Differences in male and female genital anatomy may be the reason for the rapid spread of infection to the retroperitoneum and the fatal outcome in women. Fournier's gangrene as a high-risk disease in females should attract exceeding attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
76
2
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(90 citation statements)
references
References 23 publications
(12 reference statements)
6
76
2
6
Order By: Relevance
“…The direct extension of the infection intra-abdominally through the Fallopian tubes may yield to fatal peritonitis and multi-organ failure in female patients. [43] In consistent with this data, abdominal involvement (75%) and mortality rate of female patients (25%) were higher than males in the present report.…”
Section: Ciprofloxacin 40supporting
confidence: 91%
See 1 more Smart Citation
“…The direct extension of the infection intra-abdominally through the Fallopian tubes may yield to fatal peritonitis and multi-organ failure in female patients. [43] In consistent with this data, abdominal involvement (75%) and mortality rate of female patients (25%) were higher than males in the present report.…”
Section: Ciprofloxacin 40supporting
confidence: 91%
“…In the literature, urethral catheterization, [55] vasectomy, [56,57] prostate biopsy, [58] neonatal circumcision, [35,38] hernia repair, [59,60] hemorrhoidectomy, [61] episiotomy, [62][63][64] and hysterectomy [43] were reported as surgical; anal intercourse, [65] coitus, [26,66] urethral [67,68] or anal foreign body, [69,70] penile selfinjection with cocaine, [71] heroin injection into the femoral vessels [22] and mechanical erection aid device usage [4] were reported as the non-surgical traumatic causes for FG. The source of the pathogens may be colorectal region, genitourinary tract or cutaneous flora with respect to the mechanism of trauma.…”
Section: Ciprofloxacin 40mentioning
confidence: 99%
“…They suggested that female pelvic anatomy was a disadvantage related with rapid dissemination of the disease. [15] In our serial, mortality rate for female patients was 30.8% compared to 16% in male patients. Although the mortality rate was double for female patients, female gender was not detected as a risk factor for mortality (p=0.454).…”
Section: Discussionmentioning
confidence: 49%
“…[1] Although the disease is more common among males, it has been reported that mortality due to FG is higher for females. [2][3][4] This discrepancy may be associated with anatomical differences between genders.…”
Section: Introductionmentioning
confidence: 99%
“…Anatomy of the female pelvis may also lead to rapid progression of FG and is considered to be linked to fatal peritonitis, which is associated with increased mortality. [2] Previously published studies have reported that female gender is a poor prognostic factor for FG and suggested that gender does not affect prognosis. [4][5][6][7] However, there are no published data available focusing directly on impact of gender on outcomes of FG.…”
mentioning
confidence: 99%